Association of the Affordable Care Act Medicaid Expansion With Access to and Quality of Care for Surgical Conditions - Loehrer, Andrew P. (JAMA Surg, 2018)
IMPORTANCE: Lack of insurance coverage has been associated with delays in seeking care, more complicated diseases at the time of diagnosis, and decreased likelihood of receiving optimal surgical care. The Patient Protection and Affordable Care Act’s (ACA) Medicaid expansion has increased coverage among millions of low-income Americans, but its effect on care for common surgical conditions remains unknown. OBJECTIVE: To evaluate the association of the ACA’s Medicaid expansion with access to timely and recommended care for common and serious surgical conditions. DESIGN, SETTING, AND PARTICIPANTS: This quasi-experimental, difference-in-differences study used hospital administrative data to compare patient-level outcomes in expansion vs nonexpansion states before (2010-2013) vs after (2014-2015) expansion. A total of 293 529 patients aged 18 to 64 years with appendicitis, cholecystitis, diverticulitis, peripheral artery disease (PAD), or aortic aneurysm admitted to an academic medical center or affiliated hospital in 27 Medicaid expansion states and 15 nonexpansion states from January 1, 2010, through September 31, 2015, were included in the study. Data analysis was performed from November 1, 2016, to March 3, 2017. EXPOSURES: State adoption of Medicaid expansion. MAIN OUTCOMES AND MEASURES: Presentation with early uncomplicated disease (diverticulitis without abscess, fistula, or sepsis; nonruptured aortic aneurysm at time of repair; and PAD without ulcerations or gangrene) and receipt of optimal management (cholecystectomy for acute cholecystitis, laparoscopic approach for cholecystectomy or appendectomy, and limb salvage for PAD). RESULTS: Of the 293 529 study patients (128 392 [43.7%] female and 165 137 [56.3%] male), 225 572 had admissions in Medicaid expansion states and 67 957 had admissions in nonexpansion states. Medicaid expansion was associated with a 7.5–percentage point decreased probability of patients being uninsured (95% CI, −12.2 to −2.9; P = .002) and an 8.6–percentage point increased probability of having Medicaid (95% CI, 6.1-11.1; P < .001). Medicaid expansion was associated with a 1.8–percentage point increase in the probability of early uncomplicated presentation (95% CI, 0.7-2.9; P = .001) and a 2.6–percentage point increase in the probability of receiving optimal management (95% CI, 0.8-4.4; P = .006). CONCLUSIONS AND RELEVANCE: The ACA’s Medicaid expansion was associated with increased insurance coverage and improved receipt of timely care for 5 common surgical conditions. Health care systems and policymakers should be aware of the influence of insurance coverage expansion (or its repeal) on presentation with and management of surgical disease.